Vice and Virtue in the Moral Vision of the Latin of Sirach - Gregory, Bradley C. (Biblica, 2016)
Beginning in the Second Temple period some Jewish literature begins to reflect an increased influence from Hellenistic conceptions of virtue and vice. This paper analyzes the expansions and alterations found in the Latin version of Ben Sira to show how the vices of pride, desire, and avarice are elevated in importance and integrated into the larger contours of the moral theology of the book. Their content, amount, and distribution suggest that their piecemeal production arose from attempts to integrate the virtue/vice thinking prominent in late antiquity into the teaching already found in the Book of Sirach